Inconsistências na termodinâmica de estado estacionário - Ricardo Tsuyoshi Motai (2014)
We address the issue of extending thermodynamics to nonequilibrium steady states in driven lattice gases. We examine the possibility of defining an effective chemical potential , and an effective temperature Te, via conditions of zero net flux of particles and energy between the driven system and a reservoir. For the model systems considered here, the fluxes are determined by certain average densities, eliminating the need to perturb the system by actually exchanging particles; and Te are thereby obtained via open-circuit measurements, using a virtual reservoir. For the lattice gas with nearest-neighbor exclusion, temperature is not relevant, and we find that the effective chemical potential, as a function of density and drive strength, satisfies the zeroth law, and correctly predicts the densities of systems at coexistence. In the Katz-Lebowitz-Spohn driven lattice gas, both and Te need to be defined. We show analytically that the zeroth law is violated, and determine the size of the violations via simulation. Our results highlight a fundamental inconsistency in the extension of thermodynamics to nonequilibrium steady states.